Light Field Optimization for Optical Wireless Power Transfer - Peiyuan Xu; Wenjia Zhang; Zuyuan He (IEEE Photonics Journal, 2021)
Light field manipulation is an important technology for improving system-level efficiency of optical wireless power transfer (OWPT). In this paper, we propose and compare the Gerchberg-Saxton algorithm, direct binary search and genetic algorithm enabled light field optimization for adapting photovoltaic cells in different geometric arrangements. Under static condition, photoelectric conversion efficiency can reach 33.14% through optimizing light field using Gerchberg-Saxton algorithm, almost 200% improvement over the case with Gaussian beams. Moreover, the resilience of power delivery can be improved by employing direct binary search and genetic algorithm in a dynamic fashion. By utilizing genetic algorithm optimization, initial photoelectric conversion efficiency is 14.11% with the help of random optimization process. The dynamic light field optimization technology will be an enabling technology of high efficient power delivery for mobile objects.